Directors' compensation, corporate governance and financial statement fraud: a comparative study of China and the US - Jain, Juhee (2022)
Financial statement fraud (FSF), generally committed by personnel in high ranks commanding substantial power, is regarded as one of the costliest corporate frauds which has affected both developed and developing nations. One of the reasons for the occurrence of FSF is the divergence in interests of the management (agents) and shareholders (principals). Agency theory propounds implementation of adequate compensation for achieving the alignment of interests of agents and principals. However, compensation is a double-edged sword, which may control or aggravate the incidence of FSF. Existing research has, primarily, focused on earnings management/restatement/FSF and its linkages with executive compensation. However, such analysis does not give a full picture, as directors (acting as agents of shareholders) are key monitors of the management and if they are effective in their monitoring function, then the incidence of FSF can be controlled. Hence, it is imperative that the directors’ interests are well aligned with those of the shareholders. Thus, this research attempts to view the incidence of FSF from the perspective of directors. Herein, an attempt is made to examine the causal relationship between FSF, corporate governance, and directors’ compensation and shareholding. The main objective of this study is to find out if there are any elements within the compensation packages of directors which may induce FSF. Using matched pairs methodology, this study examines the association between directors’ compensation and shareholding, corporate governance, and FSF in two of the worlds’ largest economies, China and the US as these two economies are diametrically opposite in their cultural make-up and in their institutional, political, legal, and governance orientation. China is a collectivist society whereas the US is individualistic. US follows the American corporate governance model whereas Chinese corporate governance paradigm is influenced by the German governance system. Further, in US the private sector plays a key role in the corporate sector whereas in China the state owned enterprises (SOEs) are still a dominant player in the corporate sector. This research contributes to literature on corporate governance, agency theory, institutional theory, and fraud. The results show that stock-based compensation can induce FSF. Directors’ shareholding in China and directors’ stock-based compensation in the US both have a significant positive association with the incidence of FSF, thereby implying that directors’ shareholding and stock-based compensation can induce fraud. This research finding has implications for practice as it questions the packaging of directors’ compensation and provides evidence against the use of stock-based compensation and shareholding for directors. On the governance front, the results indicate that type of auditor, CEO duality, and frequency of board meetings also influence the incidence of FSF. This research also points out that measures of good corporate governance are vital for all economies irrespective of their cultural and governance orientations. Additionally, the results of this study can be extended to other developed and developing economies operating within the same corporate governance paradigms as that of China and the US. From a theoretical perspective, this thesis provides additional evidence on agency theory, institutional theory, and the theory of fraud triangle. The results of the study indicate that monitoring mechanisms rather than compensation (specifically stock-based compensation and shareholding) are more effective in controlling the incidence of fraud as effective monitoring curbs the opportunity for fraud. Further, the efficacy of firm level monitoring/ governance holds irrespective of the institutional setting of a country. This thesis consists of three introductory chapters, three empirical essays, and a concluding chapter. Chapters 1 gives the background of the research enquiry and discusses the research agenda, research objectives, and research contribution. Chapter 2 provides a detailed review of literature covering literature on compensation, corporate governance, and financial statement fraud. Chapter 3 discusses in detail the research methodology including research philosophy, sample selection, and data analysis techniques used. Chapter 4 (Paper 1) conducts an analysis of the incidence of financial statement fraud in China using a sample of 903 fraud firms and 903 control firms during the period from 2005 to 2018. The findings indicate that directors’ shareholding is positively associated with FSF. The results also suggest that firm performance (i.e. return on assets (ROA)), board attributes (such as chief executive officer (CEO) duality, independence, and frequency of board meetings), leverage, auditor type, and ownership structure (i.e. shareholding of the top 10 shareholders) have a significant influence on FSF. Chapter 5 (Paper 2) investigates the incidence of FSF in the US using a sample of 387 fraud firms and 387 control firms during a 15 year-period from 2005 to 2019. The findings suggest that there is a positive association between the incidence of FSF and directors’ stock-based compensation, and a negative association between FSF and the average age of directors. Additionally, CEO duality, institutional ownership, firm performance (ROA), size of board of directors, size/type of auditor, frequency of board meetings, and firm size also have a significant influence on the incidence of FSF. Chapter 6 (Paper 3) undertakes a comparative analysis of China and the US in terms of their corporate governance orientation, institutional and cultural background, legal orientation and systems, and compensation practices. It also compares the fraud firms in US and China apart from identifying factors that affect the incidence of FSF in the two countries. The results suggest that firm-level variables and governance measures such as leverage, independent directors, CEO duality, frequency of board meeting, Big-4 auditor, institutional ownership, firm performance (ROA), and firm valuation (MV/BV) have a significant impact on the incidence of FSF whereas country-level variables such as culture, education, income disparity, and rule of law do not affect the incidence of FSF. The last chapter (Chapter 7) concludes the thesis by reflecting upon the key research findings, contributions of the research, and answers the research questions. It also discusses the implications, limitations, and recommendations of the research and also provides direction for future research.